2009
DOI: 10.4067/s0716-10182009000500003
|View full text |Cite
|
Sign up to set email alerts
|

La radiación a la mesa

Abstract: Radiation on the dining table Zero tolerance to bacterial contamination means considering the acceptance of "radiation on the table". The process of food irradiation has been extensively studied, nevertheless its use remains a matter of some controversy. Despite unanimous agreement within the medical community of the safety of this procedure, occasional concerns arise from the consumers. A common consumer misconception is that irradiation may turn the food "radioactive". A significant number of scientific stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(22 reference statements)
0
1
0
4
Order By: Relevance
“…The consumers of Britain were more fearful than U.S. consumers; surveys conducted in 1986 and 1988 showed that a large proportion of consumers in Britain would not buy irradiated foods (Thomas, ). In 1989, a survey by Neilson/Henry Prediction Center in the United Kingdom showed that 70% of consumers did not buy irradiated products and 20% were not sure (Rossi, Watson, Escandarani, Miranda, & Troncoso, ).…”
Section: Introductionmentioning
confidence: 99%
“…The consumers of Britain were more fearful than U.S. consumers; surveys conducted in 1986 and 1988 showed that a large proportion of consumers in Britain would not buy irradiated foods (Thomas, ). In 1989, a survey by Neilson/Henry Prediction Center in the United Kingdom showed that 70% of consumers did not buy irradiated products and 20% were not sure (Rossi, Watson, Escandarani, Miranda, & Troncoso, ).…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados permiten inferir que las características nutricionales de la papa chaucha amarilla se conservaron en ambos tratamientos durante el almacenamiento [38]. El incremento en el porcentaje de carbohidratos totales se debe a la pérdida de humedad, ya que dicho parámetro fue calculado por la diferencia del 100% y los porcentajes de los otros componentes.…”
Section: Análisis Proximalunclassified
“…Existió una buena aceptación de la papa chaucha amarilla irradiada por parte de los panelistas; algunas personas manifestaron que observaron un color amarillo más intenso en la pulpa y un sabor dulce agradable al momento de la degustación en ambas muestras tratadas (física o químicamente), lo cual indica que las características organolépticas no se vieron perjudicadas en ninguno de los dos casos [38].…”
Section: Análisis Sensorialunclassified
“…Este método ayuda a mantener los alimentos de manera más segura, hace posible conservar los mismos durante más tiempo en mejores condiciones, evita que se deterioren y echen a perder o que se produzcan condiciones no deseadas como sería la aparición de tubérculos. Destruyen algunos insectos, hongos y bacterias (63) .…”
Section: Efectos Benéficos De La Radiación Uv En Animalesunclassified